Peer Influence Among Young Adults’ Products Purchase Decisions: Examining the Influence of Peers on Young Adults' Product Choices (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper seeks to contribute tothe existing body of the literature on reference group influence. Specifically,it focuses on peer influence among young adults’ products purchasedecisions.   A convenience sample of 101university students participated in this study. The results of Analysis ofVariance and t-tests indicated that there is more normative influence for apublic luxury (sunglasses) than for a private luxury (cell phone) and privatenecessity (toothpaste). Informational influence was also more for a publicluxury than a private necessity.  Additionally, a public necessity (shoes) had more normative influencethan a private luxury and private necessity as well as a high informationalinfluence than private necessity. Overall, these results demonstrated that theinfluence of peers varies across various product categories.